102 Online Supportive Conversations & Reflection Sessions [OSCARS] with Care Home Staff Following A Resident's Death: Improving Coping Mechanisms, Team Cohesion and Communication. (16th March 2021) - Hockley, J; Johnston, L; Watson, J; Shenkin, S D
Abstract: Introduction: COVID-19 Trauma Guidance suggests opportunities for structured, time-limited discussions about challenging experiences should be offered. It is unknown if such discussions can be effectively delivered online by palliative care specialists to support care home (CH) staff in relation to death/dying. Funded by Scotland's Chief Scientist Office COVID-19 "rapid research" fund, online OSCaRS is being piloted. Methods: Fortnightly OSCaRS delivered to small groups of CH staff via a secure online platform in three local CHs over 10 weeks. Sessions are digitally recorded. The shortened version of the Chesney coping self-efficacy questionnaire is completed by all staff pre/post. Additional post-study questions asked of OSCaRS participants and in-depth staff interviews will be undertaken (n = 10). Thematic analysis of the recorded sessions and interviews will be undertaken and related to the staff questionnaire and context of each CH. Results: New learning on the feasibility and acceptability of providing OSCaRS to frontline staff. The benefit of OSCaRS to CH staff coping mechanisms, team cohesion and communicaton with relatives during the COVID-19 pandemic will be presented. Initial results show that OSCaRS are feasible, valued by all care home staff and support staff in coping with the challenges of COVID-19/. Key Conclusions: The analysis will inform future practice, and an Implementation Guide for OSCaRS in CHs will be produced. Key learning on the potential for online support in relation to death/dying during the pandemic and beyond will contribute to future education, training and staff wellbeing resources. It will also inform the role of such sessions in developing individual coping mechanisms and team working alongside communication with relatives during lockdown.